Liquidity analysis: a case study in CTRM AC Melaka / Artiqah Abdul Razak - Abdul Razak, Artiqah (Faculty of Business and Management, 2010)
CTRM Aero Composites is a subsidiary of Composites Technology Research Malaysia which is located at the Batu Berendam Melaka. The main business of CTRM AC is focusing on the manufacturing of composites components for both aerospace and non-aerospace segments. Researcher have choose liquidity analysis as the topic due to certain issues concerning on CTRM AC liquidity performance of the company. The objective of this study is to analyze the liquidity performance in order to overcome the liquidity problem. Liquidity performance is part of the financial analysis. Financial analysis is the most important way for company to analyze and evaluate the performance of the company either good or worse. One of the methods is using quantitative analysis which is ratio analysis in measure the liquidity performance of CTRM AC. Among many performance indicators of a company that can be derived from financial statements, the short-term liquidity commands a great deal of attention from both investors and management. Liquidity is company’s ability to satisfy obligation using assets that are most readily converted into cash. Assets that may be converted into cash in short time period referred to liquid assets or current assets. Current assets are often referred to as working capital, since its represent the sources need to finance day to day operation. In finding, researchers found that CTRM AC has liquidity problem especially in managing account receivable and payable. These studies suggest steps to be taken in order to overcome this liquidity problem. The managing the working capital such as inventory, receivable and payable need appropriate strategies to avoiding company having liquidity problem. Researcher also found the weaknesses of the company plus the solution towards that problem